Protective effect of the ethyl acetate fraction of Qinghai-Tibet Plateau medicinal plant Chrysosplenium axillare Maxim. against ANIT-induced cholestatic liver injury in mice - Ziyan Cai; Wenyan Li; Wei Jiang; Jixiao Zhu; Guoyue Zhong; Rongrui Wei; Zejing Mu; Gang Ren (Elsevier, 2021)
Background: Chrysosplenium axillare Maxim. has been used as a traditional Tibetan herb medicine for hepatobiliary disorder in Qinghai-Tibet Plateau for more than one thousand years. Hypothesis/purpose: we hypothesized that the ethyl acetate-soluble portion extracted from C. axillare (ECA) could exert hepatoprotection effect against α-naphthylisothiocyanate (ANIT)-induced hepatotoxity and acute intrahepatic cholestasis in mice and aimed to investigate its potential mechanism. Study design: male KM mice with acute intrahepatic cholestasis induced by ANIT were orally administered with the ECA (100 and 50 mg/kg B.W.). Mice receiving vehicle (0.5% CMC-Na) served as control. Methods: 48 h after ANIT administration, mice were sacrificed. Blood was collected for serum enzymes and components analysis using commercial kits. Livers were removed for histopathological examination and protein preparation. The protein expression levels of farnesoid X receptor (FXR), bile-salt export pump (BSEP), multidrug resistance associated protein2 (MRP2), Na+-taurocholate co-transporting polypeptide (NTCP), small heterodimer partner (SHP), and cholesterol 7α-hydroxylase (CYP7A1) were evaluated by a western blot analysis. A phytochemical analysis was conducted to characterize the chemical constituents of ECA. Results: oral administration of ECA at both doses (P < 0.05 or P < 0.01) can prevent ANIT-induced increases in levels of serum enzymes and components, including AST, ALT, ALP, DBIL, TBA, and TBIL and improve the liver pathologic change induced by ANIT exposure. Western blot analysis showed that the expression levels of FXR, BSEP, MRP2, NTCP, and SHP in ECA (100 and 50 mg/kg) groups were up-regulated versus model group (P < 0.05 or P < 0.01), and those of CYP7A1 in both ECA treated groups were down-regulated versus model group (P < 0.01). One new highly O-methylated flavonoids, chrysosplenoside I (1), together with fourteen analogues (2-15), was isolated from ECA and structurally identified by spectra analysis. Among them, the two abundant ingredients, chrysosplenosides A and I (11 and 1), were quantitatively determined to have a total content account for 32.2% of ECA. Conclusion: ECA protected against mice liver damage with acute intrahepatic cholestasis induced by ANIT via regulation of the expression of hepatic proteins involved in bile acids synthesis, transportation and re-absorption. These results confirmed the hepatoprotective efficacy of traditional Tibet herb medicine C. axillare and provided the first insight into its related mechanism as well as the potential active ingredients.